2015
DOI: 10.1002/hipo.22441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroconvulsive seizures on pattern separation

Abstract: Strategies employing different techniques to inhibit or stimulate neurogenesis have implicated a role for adult-born neurons in the therapeutic effect of antidepressant drugs, as well as a role in memory formation. Electroconvulsive seizures (ECS), an animal model of electroconvulsive therapy, robustly stimulate hippocampal neurogenesis, but it is not known how this relates to either therapeutic efficacy or unwanted cognitive side effects. We hypothesized that the ECS-derived increase in adult-born neurons wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
3
6
0
Order By: Relevance
“…This difference was observed irrespective of separations, suggesting that there was no difference in pattern separation ability between the two groups. This is in accordance with our previous study on ECS and pattern separation (Svensson et al, ), where we found that performances on minimum, medium, and maximum separations (in the TUNL task) did not differ between ECS‐ and sham‐treated groups. The TUNL and LD tasks tax pattern separation at different stages of the learning and recall process, providing different measures of pattern separation ability.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This difference was observed irrespective of separations, suggesting that there was no difference in pattern separation ability between the two groups. This is in accordance with our previous study on ECS and pattern separation (Svensson et al, ), where we found that performances on minimum, medium, and maximum separations (in the TUNL task) did not differ between ECS‐ and sham‐treated groups. The TUNL and LD tasks tax pattern separation at different stages of the learning and recall process, providing different measures of pattern separation ability.…”
Section: Discussionsupporting
confidence: 93%
“…4a-c). The choice accuracy and the number of trials and reversals, were generally higher in the maximum separation condition compared with the medium separation condition and lowest in the minimum separation condition, as would be expected since performances on minimum separations place higher demands on hippocampal function (Svensson et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Weight was recorded twice; in the beginning and at the end of the experiment. We have in our previous studies used this method to analyse weight gain, and by ‘mixed-design’ we mean that the ANOVA consisted of both within-subject and between-subject factors (29). In statistical follow-up analyses, a linear regression analysis was used to calculate weight gain.…”
Section: Methodsmentioning
confidence: 99%